2021
DOI: 10.1007/s10948-021-05970-3
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of Structural, Electronic, Optical, and Thermoelectric Properties of LuNiBi and LuNiSb Half-Heusler

Abstract: The structural, electronic, optical, and thermo-electric properties of LuNiBi and LuNiSb Half-Heusler have been studied using a full potential linearized augmented plane-wave (FP-LAPW) method. The results of the calculations presented in this work were obtained through the use of different approximations GGA-PBE, GGA-PBEsol, GGA-WC, and mBJ-GGA. The electronic band structures exhibit that the LuNiBi and LuNiSb alloys have a small indirect gaps in the valence band and the conduction band at points Г and X, reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
(52 reference statements)
3
11
0
Order By: Relevance
“…For LuPtSb the electronic states of the VB and CB just touch the Fermi level ( E F ) at the Γ point of the Brillouin zone which shows it is a gapless semiconductor. Our calculated values of E g are in good agreement with experimental 27,32,40,41 and other theoretical 34,35,37,48,49 results and are presented in Table 2. We found that by the replacement of Ni by Pd and then Pd by Pt, the value of band gap decreases.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…For LuPtSb the electronic states of the VB and CB just touch the Fermi level ( E F ) at the Γ point of the Brillouin zone which shows it is a gapless semiconductor. Our calculated values of E g are in good agreement with experimental 27,32,40,41 and other theoretical 34,35,37,48,49 results and are presented in Table 2. We found that by the replacement of Ni by Pd and then Pd by Pt, the value of band gap decreases.…”
Section: Resultssupporting
confidence: 86%
“…49 6.451 49 Note: Available results from experiments and other calculations are also listed. with experimental 27,32,40,41 and other theoretical 34,35,37,48,49 results…”
Section: Band Structuresupporting
confidence: 59%
See 2 more Smart Citations
“…It crystallizes in MgAgAs type structure, with space group F43m (216) and the atomic positions of Tb, Ni, and Sb atoms are (0,0,0), (1/4,1/4,1/4) and (1/2,1/2,1/2), respectively. Various experimental and theoretical studies on HH compound have been reported [11][12][13][14][15][16]. Ciesielski et al [11] experimentally studied the high temperature thermoelectric application of HH RENiSb (RE= Sc, Dy, Ho, Er, Tm, Lu) compounds and concluded that by properly adjusting carrier concentration and lowering their thermal conductance through appropriate alloying or nano structuring, the RENiSb phases are excellent candidates to provide great thermoelectric efficiency at high temperatures.…”
Section: Introductionmentioning
confidence: 99%